2005
DOI: 10.1227/01.neu.0000154699.29796.34
|View full text |Cite
|
Sign up to set email alerts
|

Facial and Cochlear Nerve Function after Surgery of Cerebellopontine Angle Meningiomas

Abstract: Although the outcome of facial and cochlear nerve function is different in CPA meningiomas, depending on the topographic classification of these tumors, preservation of the cochlear nerve is possible in every tumor group and should be attempted in every patient with CPA meningioma. It has to be kept in mind that recovery of hearing was also observed in patients with preoperative profound hearing deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 25 publications
(30 reference statements)
1
64
0
5
Order By: Relevance
“…1,10,14,16 Multiple factors, including preoperative facial nerve status, surgical approach, anatomical location, and involvement of the IAC, likely contribute to perioperative CN VII dysfunction. 1,10,17,18,23 In the study by Agarwal et al, permanent CN complications were reported in 5.9% patients with tumors smaller than 3 cm and in 45.5% of the cases in which the lesions were larger than 3 cm and were more frequent in those undergoing STR than in those undergoing GTR. 1 Similarly, Leonetti et al reported permanent postoperative complications in 8 (27.6%) patients, with CN VII dysfunction specifically being reported in 3 (10.3%) patients.…”
Section: 25mentioning
confidence: 95%
“…1,10,14,16 Multiple factors, including preoperative facial nerve status, surgical approach, anatomical location, and involvement of the IAC, likely contribute to perioperative CN VII dysfunction. 1,10,17,18,23 In the study by Agarwal et al, permanent CN complications were reported in 5.9% patients with tumors smaller than 3 cm and in 45.5% of the cases in which the lesions were larger than 3 cm and were more frequent in those undergoing STR than in those undergoing GTR. 1 Similarly, Leonetti et al reported permanent postoperative complications in 8 (27.6%) patients, with CN VII dysfunction specifically being reported in 3 (10.3%) patients.…”
Section: 25mentioning
confidence: 95%
“…6 Compared with VS, meningiomas are the next most common CPA tumor constituting 10% to 15% of all CPA tumors. 1 The treatment and operative approach differ for VS and meningioma, and consequently an accurate preoperative diagnosis is warranted to distinguish these 2 tumors. 7 Meningiomas seem to offer better chances to preserve hearing than VS. 1,7 An accurate preoperative diagnosis may influence the prognosis because meningiomas are known to have a higher incidence of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…1 The treatment and operative approach differ for VS and meningioma, and consequently an accurate preoperative diagnosis is warranted to distinguish these 2 tumors. 7 Meningiomas seem to offer better chances to preserve hearing than VS. 1,7 An accurate preoperative diagnosis may influence the prognosis because meningiomas are known to have a higher incidence of recurrence. 7 Multiplanar capability, superior soft tissue contrast resolution, and lack of beam hardening artifacts make MR imaging the preferred technique to assess CPA tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations